Effect of Hearing Device Use on Speech-in-Noise Performance in Children with Severe-to-Profound Unilateral Hearing Loss. Issue 3 (28th December 2022) - Griffin, Amanda M.; Atri, Ava; Licameli, Greg; Stiles, Derek J.
Abstract : Objectives: Limited evidence exists for the use of rerouting devices in children with severe-to-profound unilateral sensorineural hearing loss. Many laboratory studies to date have evaluated hearing-in-noise performance in specific target-masker spatial configurations within a small group of participants and with only a subset of available hearing devices. In the present study, the efficacy of all major types of nonsurgical devices was evaluated within a larger group of pediatric subjects on a challenging speech-in-noise recognition task. Design: Children (7–18 years) with unaided severe-to-profound unilateral hearing loss (UHL‚ n = 36) or bilateral normal hearing (NH, n = 36) participated in the present study. The signal-to-noise ratio (SNR) required for 50% speech understanding (SNR-50) was measured using BKB sentences in the presence of proprietary restaurant noise (R-SPACE BSIN-R) in the R-SPACE Sound System. Subjects listened under 2 target/masker spatial configurations. The target signal was directed toward subjects' NH or hearing-impaired ear (45º azimuth), while the interfering restaurant noise masker was presented from the remaining 7 loudspeakers encircling the subject, spaced every 45º. Head position was fixed during testing. The presentation level of target sentences and masking noise varied over time to estimate the SNR-50 (dB). The following devices were tested in all participants with severe-to-profound UHL: air conduction (AC) contralateral routing of signal (CROS), bone conduction (BC) CROS fitted on a headband with and without the use of remote microphone (RM), and an ear-level RM hearing assistance technology (HAT) system. Results: As a group, participants with severe-to-profound UHL performed best when the target signal was directed toward their NH ear. Across listening conditions, there was an average 8.5 dB improvement in SNR-50 by simply orienting the NH ear toward the target signal. When unaided, participants with severe-to-profound UHL performed as well as participants with NH when the target signal was directed toward the NH ear. Performance was negatively affected by AC CROS when the target signal was directed toward the NH ear, whereas no statistically significant change in performance was observed when using BC CROS. When the target signal was directed toward participants' hearing-impaired ear, all tested devices improved SNR-50 compared with the unaided condition, with small improvements (1–2 dB) observed with CROS devices and the largest improvement (9 dB) gained with the personal ear-level RM HAT system. No added benefit nor decrement was observed when RM was added to BC CROS using a 50/50 mixing ratio when the target was directed toward the impaired ear. Conclusions: In a challenging listening environment with diffuse restaurant noise, SNR-50 was most improved in the study sample when using a personal ear-level RM HAT system. Although tested rerouting devices offered measurable improvement in performance (1–2 dB in SNR-50) when the target was directed to the impaired ear, benefit may be offset by a detriment in performance in the opposing condition. Findings continue to support use of RM HAT for children with severe-to-profound UHL in adverse listening environments, when there is one primary talker of interest, to ensure advantageous SNRs.